Dinámica del nitrógeno en el suelo de un encinar montano : respuesta a una perturbación experimental - Bonilla D.; Rodá F. (Jornadas sobre las bases ecológicas para la gestión en ecosistemas terrestres, 1989)
In March 1986, four 2x2 m treeless plots were trenched all around in an evergreen oak stand in the Montseny mountains (NE Spain). Responses to perturbation were monitorised through: 1) net mineralisation and nitrification rates measured monthly in situ incubation in polyethylene bags (020 cm); 2) N03- concentration in soil solution. In control plots, 80 kg N/ha/year were mineralised and 9 per cent of them were nitrificated. In trenched plots 325 kg N/ha/year were mineralised and 73 per cent of them were nitrificated. The results obtained in control and trenched plots reveal the potential for very high nitrate losses following disturbance.
Jornadas sobre las Bases Ecológicas para la Gestión en Ecosistemas Terrestres, 1988/06/13-15, Zaragoza (Spain)